Analysis of Symbol in Westlife Coast to Coast Album - Mac Aditiawarman; Sonya Putri Rahmadani (Fakultas Sastra Universitas Ekasakti, 2020)
Song is a series of words that are obtained from the inspiration of everyday life. a series of words arranged in such a way that they contain rhythm and meaning that will be conveyed to the listener. Songs are part of literary works. Listening to songs is a very fun activity. sometimes the listener just listens to it and doesn't understand the symbols and meanings in the song. sometimes the song consists of symbols to describe the feelings of the composer. Based on the reason, it brought the reseasrcher to find out the symbol and application of Symbol in the song lyrics and To explain the meaning songs in Westlife’s Coast to Coast Album. This research applied a descriptive qualitative method. Through this method the researcher Tried to analyze, explain,and find out the symbols by using Charles Sanders Pierce’s theory. In this case, Charles Sanders Pierce developed a triadic model in illustrating the definition of the sign as a symbol. The triadic model consisted of three components; representamen, object and interpretant. In this research researcher taken the specific objects of the analysis were songs from Westlife the name of album was Coast to Coast. The song consist of seventeen songs, there were My love, What makes a man, I lay my love on you, When you’re looking like that, Close, Somebody needs you, Angel’s wing’s, Soledad, Puzzle of my heart, Dreams come true, No place that far, close your eyes, You make me feel, Loneliness knows me by name, Fragile heart, Every little thing you do, Uptown girl. The symbols found are empty heart, enthusiasm, spirit, motivation, loyalty, simplicity, strength, happiness, and sadness. Every lyrics written must have a message aimed at both listeners and readers. The message is directed with the intention of making them impress after listening to and reading the lyrics.